Phase I metabolism of the carbazole‐derived synthetic cannabinoids EG‐018, EG‐2201, and MDMB‐CHMCZCA and detection in human urine samples. Issue 9 (23rd May 2018) - Mogler, Lukas; Franz, Florian; Wilde, Maurice; Huppertz, Laura M.; Halter, Sebastian; Angerer, Verena; Moosmann, Bjoern; Auwärter, Volker
Abstract: Synthetic cannabinoids (SCs) are a structurally diverse class of new psychoactive substances. Most SCs used for recreational purposes are based on indole or indazole core structures. EG‐018 (naphthalen‐1‐yl(9‐pentyl‐9 H ‐carbazol‐3‐yl)methanone), EG‐2201 ((9‐(5‐fluoropentyl)‐9 H ‐carbazol‐3‐yl)(naphthalen‐1‐yl)methanone), and MDMB‐CHMCZCA (methyl 2‐(9‐(cyclohexylmethyl)‐9 H ‐carbazole‐3‐carboxamido)‐3, 3‐dimethylbutanoate) are 3 representatives of a structural subclass of SCs, characterized by a carbazole core system. In vitro and in vivo phase I metabolism studies were conducted to identify the most suitable metabolites for the detection of these substances in urine screening. Detection and characterization of metabolites were performed by liquid chromatography–electrospray ionization–tandem mass spectrometry (LC–ESI–MS/MS) and liquid chromatography–electrospray ionization–quadrupole time‐of‐flight–mass spectrometry (LC–ESI–QToF–MS). Eleven in vivo metabolites were detected in urine samples positive for metabolites of EG‐018 ( n = 8). A hydroxypentyl metabolite, most probably the 4‐hydroxypentyl isomer, and an N ‐dealkylated metabolite mono‐hydroxylated at the carbazole core system were most abundant. In vitro studies of EG‐018 and EG‐2201 indicated that oxidative defluorination of the 5‐fluoropentyl side chain of EG‐2201 as well as dealkylation led to common metabolites with EG‐018. This has to be taken into account for interpretation of analytical findings. A differentiation between EG‐018 and EG‐2201 ( n = 1) uptake is possible by the detection of compound‐specific in vivo phase I metabolites evaluated in this study. Out of 30 metabolites detected in urine samples of MDMB‐CHMCZCA users ( n = 20), a metabolite mono‐hydroxylated at the cyclohexyl methyl tail is considered the most suitable compound‐specific consumption marker while a biotransformation product of mono‐hydroxylation in combination with hydrolysis of the terminal methyl ester function provides best sensitivity due to its high abundance. Abstract : EG‐018, EG‐2201, and MDMB‐CHMCZCA are recently emerged synthetic cannabinoids featuring carbazole core structures. Analytical methods were developed for the detection of the metabolites of these substances in human urine samples. With LC–MS/MS and LC–QToF–MS techniques the main in vivo and in vitro phase I metabolites were detected and evaluated as consumption markers.